Automation tool for role transition in oracle data guard databases by adopting oracle best known practices / Sathis Krishnan - Sathis , Krishnan (2019)
Database availability is utmost critical factor for most of the businesses to sustain and continue their business. The required availability varies within an organization and unavailability is intolerable. Failed role transition is one of the causes for the unavailability. The predominant Oracle software with Data Guard databases versions is commonly used to run the most demanding, mission-critical database driven applications such as manufacturing, e-banking, etc. In this complex administration of Oracle Data Guard environment maintaining and executing an efficient role transition requires an automated tool to optimize an error free role transition. Having discovered by the survey result which conducted to a group of database administrators, there is a need for the database administrators to have an automated tool to perform the role transition more efficient and error free. With an assessment of the Oracle Data Guard database, we have developed an approach for an efficient role transition of Oracle Data Guard database in term of the architecture concept and components, best practices and their impact on role transition. The approach consists of role transition, implemented with a custom developed tool, and prerequisite and post task of role transitions using the recommended Oracle best practices. The approach is designed by doing a comparative study of existing Oracle best practices and interviewing database administrators. The approach consists of prerequisite and post task of role transition such as verify configuration health check, ensure no redo log transmission gap between primary and standby database, overall health check of production database and its standby databases and other checks. Finally, an evaluation between the existing methods and the proposed approach one is provided based on how they solve the Oracle Data Guard role transitions gaps with considering the external factors challenges and the degree of automation provided. The results of the study show the proposed a role transition approached, a set of SQL query scripts integrated in a custom designed Perl tool and demonstrated how the tool helped to automate the role transition process. It has significantly reduced the time taken to perform the role transition up to 80% with 99% successful role transition. Moreover, the Oracle Database Automated Role Transition (ODaRT) ease the routine task database administrator and helpful for the novice to perform error free role transition.